THE INFLUENCE OF PRODUCT PLACEMENT, CELEBRITY ENDORSEMENT, AND BRAND INTEGRATION IN KOREAN DRAMAS ON BRAND RECOGNITION AT KOPIKO PRODUCT AND BRAND IMAGE AS MEDIATING - Wulandari, Sukma; Setiawan, Harry; Afifah, Nur; Purmono, Bintoro Bagus (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to analyze the influence of product placement, celebrity endorsement, and brand integration in Korean dramas on brand recognition using a brand image as a mediating variable. This research responds to the growing popularity of Korean dramas as a cross-cultural marketing platform, especially for the Indonesian coffee candy brand Kopiko. The research approach used was quantitative, with a total of 230 respondents who watched Korean dramas featuring Kopiko, and the data were analyzed using structural equation modeling (SEM). The results show that product placement, celebrity endorsement, and brand integration have a positive impact on brand recognition, with brand image playing an important mediating role. This research provides valuable insights for international marketers, demonstrating that strategic placement in high-engagement media can enhance brand image and recognition. Future research could explore broader applicability in digital media and evaluate the effectiveness of these strategies in different cultural markets.